Exploring Identities of Extension Faculty and Educators as Science Communicators - Klae O'Brien; Carrie N Baker; Sarah A. Bush; Maggie Elliot; Kattlyn J Wolf (Journal of Applied Communications, 2024)
This research explored the relationship between University of Idaho (UI) Extension educators and faculty’s social identity as science communicators and their most-used communication type. This non-experimental, sequential, mixed-method study with a qualitative priority utilized surveys and interviews to gather data. This paper will focus on the qualitative and mixing components of the study. We used stratified purposive sampling based on location and most used communication type to select participants for interviews and conducted interviews to understand their social identities as science communicators. We identified five main themes: continual development, technology, research dissemination, evaluation for motivation, and community relationships. We employed a cross-case comparison to find relationships between themes and communication type. Science communication identity and communication types have distinct relationships with science communication identity being seen as an adaptable and flexible title. Participants reported diverse motivations for communicating science, but all emphasized their roles in sharing reliable, research-based information with constituents. Participants discussed the value of skill-building and expressed interest in additional training to become more effective science communicators and better meet the needs of the communities they serve. Additional research to understand the constituent perspective is warranted to explore how professionals are using science communication practices to align with the communication preferences of their audiences to achieve intended outcomes. Replicating this study with Extension professionals in other states would provide insight into a national understanding and application of science communication in Extension.
Keywords: Extension; science communication; social identity; community; mixed methods